2014
DOI: 10.1373/clinchem.2013.215079
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Viable Circulating Tumor Cells Detected by EPISPOT in Metastatic Breast Cancer Patients

Abstract: BACKGROUND: Detection of circulating tumor cells (CTC) in breast cancer patients is currently performed in many clinical trials, using different technologies, in particular the EpCAM-dependent CellSearch® system. The purpose of this study was to investigate the incidence and prognostic relevance of viable CTC in a large cohort of metastatic breast cancer (MBC) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 24 publications
2
62
0
Order By: Relevance
“…Short-term cultures of CTCs have become possible by the EPISPOT assay 10 years ago (9); this assay detects specific proteins secreted during the in vitro culture of CTCs (10), and clinical studies in breast and colon cancer indicate that the detection of viable CTCs is associated with an unfavorable outcome (11,12). First ex vivo expansion of CTCs has been described in breast cancer by Zhang and colleagues (13) and more recently by Yu and colleagues (14).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term cultures of CTCs have become possible by the EPISPOT assay 10 years ago (9); this assay detects specific proteins secreted during the in vitro culture of CTCs (10), and clinical studies in breast and colon cancer indicate that the detection of viable CTCs is associated with an unfavorable outcome (11,12). First ex vivo expansion of CTCs has been described in breast cancer by Zhang and colleagues (13) and more recently by Yu and colleagues (14).…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach (CD45 depletion) is used in the so-called EPISPOT assay [10,11]. However, this assay requires technically challenging detection and nonstandard equipment for subsequent detection.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only existing functional test that has been used on hundreds of patients with different tumor types is EPISPOT, which allows the detection of viable clinically relevant CTCs enriched by leukocyte depletion (23,24 ). This technology enables the detection of EpCAM ϩ and EpCAM Ϫ CTCs.…”
Section: Detection Of Viable Ctcsmentioning
confidence: 99%
“…Cells are cultured for a short time on a membrane coated with antibodies that capture the secreted/released/shed tumorassociated proteins, which are subsequently detected by secondary antibodies labeled with fluorochromes. For breast cancer, cytokeratin 19 (CK19), HER2, cathepsin D, and MUC-1 have been used as marker proteins, and the associated clinical data have shown that patients with CK19-releasing cells had an unfavorable outcome (24,25 ). For prostate cancer, prostate-specific antigen has been used for CTC detection and fibroblast growth factor 2 as stem cell growth factor for further characterization (26 ).…”
Section: Detection Of Viable Ctcsmentioning
confidence: 99%